HOUSEHOLD DIGITAL MEDIA ECOLOGIES - METHODOLOGICAL INNOVATIONS FOR FOSTERING RESEARCHER-PARTICIPANT TRUST - Kennedy, Jenny; Wilken, Rowan; Nansen, Bjorn; Arnold, Michael; Gibbs, Martin (AoIR Selected Papers of Internet Research, 2019)
In this paper, we describe a research methodology we have developed, based upon digital ethnography approaches, and which used mobile devices, digital ethnographic software and creative data collection activities. Our approach, refined over the course of a number of interconnected research projects, addressed these difficulties through a staged process – utilising traditional ethnographic techniques, but augmenting them with something more novel: the “domestic probe”. In essence, the domestic probe comprised a box of equipment given to the household to use in order to record and interpret their use of domestic technologies. In more recent work, we extended our participatory approach through the use of digital media, such as by using iPad minis pre-loaded with a data collection software tool, Ethnocorder. As we argue in this paper, these approaches carry three specific trust-related methodological benefits (and challenges): the foster trust in us as researchers; trust in our participants as co-researchers; and, as a result of this mutual researcher-participant trust, insight and a productive point of entry into discussing participant "domestication" of, and trust in, various household technologies.